Fabrication and characterization of relaxor ferroelectric material - Lin, Aylwin Kui An. (2009)
Fabrication of environmental friendly relaxor ferroelectric material without the presence of lead has attracted great number of research interests due to its high dielectric constants, electromechanical coupling factor and it potential application on transducers and actuators. This report will focus on the fabrication of a lead-free relaxor ferroelectric bulk and thin film based on FeTiTaO6. Relaxor ferroelectric ceramics, FeTiTaO6, were synthesized using conventional solid state synthesis method under different sintering conditions and the dielectric properties were investigated by capacitance analysis. Density levels, phase structure and dielectric properties of FeTiTaO6 was investigated accordingly. Initial explorations on the fabrication and characterization of FeTiTaO6 thin films hase been done on Pulse Laser Deposition (PLD). Challenges faced by the author during the research would be stressed upon and remedy actions are taken to overcome them. Sintering process for lead-free relaxor ferroelectric FeTiTaO6 bulk fabrication has been successfully developed and a high degree of rutile phase obtained was confirmed by XRD measurements. The largest real part of the dielectric permittivity ( ’) obtained from the bulk without undergoing repeated grinding and sintering is in the order of 7.5*108 and it was found to undergo a diffuse phase transition which is consistent with the properties of relaxor ferroelectrics. The phase transition region of the bulk was also noticed to shift towards higher temperature as the grain size increased. Sintering conditions used was 1300oC for 10hr having a density level of 95.61% and 73.2% rutile phase was present. FeTiTaO6 bulk has clearly display relaxor ferroelectric behavior. FeTiTaO6 thin film was successfully fabricated using Pulse Laser Deposition technique. Epitaxial thin film was achieved on Sapphire (102) substrate and a polycrystalline film was achieved on Silicon substrate. Dielectric measurements of the thin films are seen to deviate from the bulk relaxor properties due to the non stoichiometry of the film, substrate clamping effect and the large leakage current exhibited.